2016
DOI: 10.1186/s12967-016-0853-5
|View full text |Cite
|
Sign up to set email alerts
|

The MHC-II transactivator CIITA inhibits Tat function and HIV-1 replication in human myeloid cells

Abstract: BackgroundWe previously demonstrated that the HLA class II transactivator CIITA inhibits HIV-1 replication in T cells by competing with the viral transactivator Tat for the binding to Cyclin T1 subunit of the P-TEFb complex. Here, we analyzed the anti-viral function of CIITA in myeloid cells, another relevant HIV-1 target cell type. We sinvestigated clones of the U937 promonocytic cell line, either permissive (Plus) or non-permissive (Minus) to HIV-1 replication. This different phenotype has been associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…In this regard, we have earlier shown that TRIM22 interferes with Sp1 driven proviral transcription 31 , 32 whereas other investigators have reported its negative effects also in MDM 53 , 54 . CIITA, in addition to its key role of the upregulation of MHC Class II antigens 55 , was demonstrated to compete with Tat for binding to the P-TEFb complex 56 , also in myeloid cells 33 , thereby resulting in the downregulation of HIV-1 gene expression. More recently, we have reported that TRIM22 and CIITA can aggregate in nuclear bodies also containing TRIM19/PML and Cyclin T1 (a component of the P-TEFb complex) 34 suggesting that these factors may act in concert.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, we have earlier shown that TRIM22 interferes with Sp1 driven proviral transcription 31 , 32 whereas other investigators have reported its negative effects also in MDM 53 , 54 . CIITA, in addition to its key role of the upregulation of MHC Class II antigens 55 , was demonstrated to compete with Tat for binding to the P-TEFb complex 56 , also in myeloid cells 33 , thereby resulting in the downregulation of HIV-1 gene expression. More recently, we have reported that TRIM22 and CIITA can aggregate in nuclear bodies also containing TRIM19/PML and Cyclin T1 (a component of the P-TEFb complex) 34 suggesting that these factors may act in concert.…”
Section: Discussionmentioning
confidence: 99%
“…By regulating the expression of all MHC class II genes, CIITA controls antigen presentation to CD4+ T helper (TH) cells, thus playing a critical role in the triggering of the adaptive immune response against a wide variety of antigens including pathogens ( 48 , 49 ) and tumors ( 50 ). CIITA is a large protein characterized by distinct functional domains critical for its transactivating function: the N-terminal transcription activation domain (AD); the proline/serine/threonine-rich region (P/S/T); the GTP-binding domain (GBD), and the C-terminal leucine-rich repeats (LRR) important for the subcellular localization of the protein ( 51 53 ).…”
Section: Mechanisms Of Trim22 and Ciita Viral Restrictionmentioning
confidence: 99%
“…Here, CIITA exerts its inhibitory function mainly by retaining Tax-1-NF-kB complex in the cytoplasm, thus preventing the translocation of NF-kB to the nucleus and the consequent activation of NF-kB responsive genes. In this regard, CIITA may counteract the oncogenic potential of HTLV-1 ( 52 , 53 ).…”
Section: Mechanisms Of Trim22 and Ciita Viral Restrictionmentioning
confidence: 99%
“…We have previously characterized TRIM22 as an epigenetic repressor of HIV-1 transcription and replication in both primary PBMC (Ghezzi et al, 2013) and cell lines of both myeloid and T lymphocytic origin (Forlani et al, 2016;Kajaste-Rudnitski et al, 2011;Turrini et al, 2015). Furthermore, TRIM22 inhibited the replication of a TAR/Tatindependent, Dox-dependent virus variant (HIV-rtTA) mainly by interfering with Sp1-dependent transcription (Turrini et al, 2015).…”
Section: Trim22-kd Enhances Dox-dependent Proviral Reactivation and Vmentioning
confidence: 99%
“…In particular, we have described that, even in the absence of a direct interaction with proviral DNA, TRIM22 specifically inhibits the binding of the cellular transcription factor Specificity protein 1 (Sp1) to the HIV-1 LTR promoter region in vitro (Turrini et al, 2015). Furthermore, TRIM22 was shown to localize in specific nuclear structure, termed "TRIM22 nuclear bodies", also containing the HIV-1 transcriptional repressors TRIM19/Promyelocytic leukemia (PML), Cyclin T1, a crucial component of the P-TEFb complex, and Class II Transactivator (CIITA), a transcriptional repressor of HIV-1 proviral transcription (Forlani et al, , 2016. Based on these observations, TRIM22 nuclear bodies have been suggested to represent an example of intracellular hub of antiviral factors, inhibiting both the basal and Tat-dependent HIV-1 transcription .…”
Section: Introductionmentioning
confidence: 99%